¿Una teoría de las cinco sustancias en Marsilio Ficino? = A theory of five substances in Marsilio Ficino’s thought? - Rodríguez, Teresa (Veritas, 2020)
In this paper I explore the so-called theory of five substances that has characterized the traditional interpretation of Ficino’s ontology since Kristeller published his book The philosophy of Marsilio Ficino. My point of departure is the first chapter of Book I of his Platonic Theology. I seek to demonstrate that it is not clear that the five degrees of reality can be identified as “substances” in Ficino’s text. From the comparison of this chapter with certain passages in his Parmenides’ Commentary, I propose that it is more appropriate to describe only the first three degrees as “substances”. Therefore, the traditional interpretation of Ficino’s ontology is not accurate